Solar Corn Sheller Machine Design Based on Ergonomics Principles - Endro Prihastono; Antoni Yohanes; Firman Ardiansyah Ekoanindiyo (Jurnal Serambi Engineering, 2023)
The existing sheller machine on the market still uses diesel fuel and electricity, even though diesel fuel has increased. Solar is a non-renewable energy. In addition, there is a new modification of the corn sheller machine with solar power to replace diesel fuel. The fuel replacement is focused on the utilization of sunlight. This corn sheller machine can replace the use of fossil raw materials and electricity with solar power and obtain faster, more ergonomic product results. The data required in this study are body dimension data or shoulder height anthropometry in an upright standing position to determine the height of the corn sheller that will be done standing when the farmer does the corn shelling process. With the existence of a solar-powered corn sheller machine, it is expected to be more productive than before. The transition to the use of environmentally friendly (pollution-free) corn sheller machines so as to reduce air pollution that previously used motor engines with fossil fuels, namely diesel, corn farmers can understand about work comfort, are able to operate environmentally friendly corn sheller machines and can carry out maintenance procedures for solar corn sheller machines.